A Novel Concept for Hybrid Unmanned Aerial Underwater Vehicles Focused on Aquatic Performance - Horn, Alexandre; Pinheiro, Pedro; Grando, Ricardo; da Silva, Cesar; A. Neto, Armando; Drews-Jr, Paulo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
This paper presents the HyDrone, a novel concept of hybrid vehicle for aerial and underwater applications. Here, we discuss its geometry and dynamical behavior, concerning their main advantages and constraints. Translation and rotation models in SE(3) are presented, with the respective control laws used to stabilize the system in the air and under the water. Similar to other air/water vehicles in the literature, our robot can also navigate in both environments without mechanical adaptation during the medium transitions. However, our vehicle provides better results when compared to other approaches in the stateof-the-art in terms of underwater navigation efficiency. Simulated results demonstrate the trade-offs associated with our new hybrid platform when compared to other existing hybrid vehicles.